Dolabellane Diterpenoids from the South Atlantic Gorgonian Convexella magelhaenica - Rojo De Almeida, María Tereza (2010)
Two new dolabellane diterpenoids (1 and 2) were isolated from a small sample of the deep water gorgonian octocoral Convexella magelhaenica collected as a nontarget by-catch by dredging (−93 m) in commercial Patagonian scallop fishing grounds in the South Atlantic. The structures of the new compounds, which are major metabolites in the extract, were established by spectroscopic techniques and chemical transformations. Both compounds were cytotoxic against a human pancreatic adenocarcinoma cell line at micromolar concentrations.